Reducing the Footprint of Growth - World Bank (Washington, DC, 2014)
Reducing the footprint of growth requires a focus on three key issues: a) transforming urban areas into greener, more efficient, resilient, and socially inclusive cities, better able to capture the economic benefits associated with urbanization; b) ensuring sound management of the brown environmental agenda to provide the conditions for continued sustainable economic green growth while preventing and minimizing negative impacts and risks for human health and the environment; and c) promoting energy efficiency in housing, transport, urban infrastructure, and waste management to enhance the sustainability and competitiveness of the Mexican economy.